Lowered heart rate response during competition in figure skaters with greater aerobic fitness - Medeiros, A. R.; Tonello, L.; Gasparini, N.; Foster, C.; Boullosa, D. A. (International Journal of Performance Analysis in Sport, 2016)
The purpose of this study was to compare the cardiovascular stress responses to a simulated and a real competition in female artistic roller skaters; and to evaluate the potential influence of aerobic fitness on these responses. Eleven competitive female figure skaters recorded their heart rate during the same figure skating program under real and simulated competitive situations. Mean heart rate and the area under the heart rate curve method analyses were compared between conditions and correlated with maximum oxygen consumption (VO2max). There were significant differences between training and competition for mean heart rate (p=0.044) and area under the heart rate curve (p=0.002). A significant negative correlation between the estimated VO2max and the delta of the area under the heart rate curve (r = - 0.867, p = 0.001) was also revealed. These findings suggest that competition induces a greater heart rate response during a figure skating program when compared to a simulated competition. A greater aerobic fitness might attenuate this greater heart rate response. The area under the heart rate curve method is a simple and effective method for detecting differences in cardiac stress between exercises with different psycho-physiological demands.